link between SIN1 (MAPKAP1) and poly(rC) binding protein 2 (PCBP2) in counteracting environmental stress - Ghosh, Debjani; Srivastava, Gyan P; Xu, Dong; Schulz, Laura C; Roberts, R. Michael (Proceedings of the National Academy of Sciences - PNAS, 2008)
When SIN1 (MAPKAP1) was used as the bait in a two-hybrid screen of a human bone marrow cDNA library, its most frequent partner was poly(rC) binding protein 2 (PCBP2/hnRNP-E2), which associates with the N-terminal domain of SIN1 and can be coimmunoprecipitated with SIN1 and the cytoplasmic domain of the IFN receptor IFNAR2 from HeLa cells. SIN1, but not PCBP2, also associates with the receptors that bind TNFα. PCBP2 is known to bind pyrimidine-rich repeats within the 3' UTR of mRNAs and has been implicated in control of RNA stability and translation and selective cap-independent transcription. RNAi silencing of either SIN1 or PCBP2 renders cells sensitive to basal and stress-induced apoptosis. Stress in the form of TNFα and H₂O₂ treatments rapidly raises the cell content of SIN1 and PCBP2, an effect reversible by inhibiting MAPK14. A meta analysis of human microarray information with an algorithm that discerns similarities in gene-regulatory profiles shows that SIN1 and PCBP2 are generally coregulated with large numbers of genes implicated in both cell survival and death and in cellular stress responses, including RNA translation and processing. We predict that SIN1 is a scaffold protein that organizes antiapoptotic responses in stressed cells, whereas PCBP2, its binding partner, provides for the selective expression of cell survival factors through posttranslational events.